Comparison of Femoral and Axillary Artery Cannulation in Acute Type A Aortic Dissection Surgery - Orhan Gokalp (Brazilian Journal of Cardiovascular Surgery, 2019)
Abstract Introduction: One of the most important points of the acute type A aortic dissection surgery is how to perform cannulation regarding cerebral protection concerns and the conditions of arterial structures as a pathophysiological consequence of the disease. Objective: In this study, femoral and axillary cannulation methods were compared in acute type A aortic dissection operations. Methods: The study retrospectively evaluated 52 patients who underwent emergency surgery for acute type A aortic dissection. Patients without malperfusion according to Penn Aa classification were chosen for preoperative standardization of the study groups. The femoral arterial cannulation group was group 1 (n=22) and the axillary arterial cannulation group was group 2 (n=30). The groups were compared in terms of perioperative and postoperative results. Results: There was no statistically significant difference in terms of preoperative data. In terms of postoperative parameters, especially early mortality and new-onset cerebrovascular event, there was no statistically significant difference. Mortality rates in group 1 and group 2 were 13.6% (n=3) and 10% (n=3), respectively (P=0.685). Postoperative new-onset cerebral events ratio was found in 5 (22.7%) in the femoral cannulation group and 6 (20%) in the axillary cannulation group (P=0.812). Conclusion: Both femoral and axillary arterial cannulation methods can be safely performed in patients with acute type A aortic dissection, provided that cerebral protection strategies should be considered in the first place. The method to be performed may vary depending on the patient’s current medical condition or the surgeon's preference.